Oceanic cephalopod distribution and species diversity in the eastern north Atlantic. - Clarke, Malcolm R. (Universidade dos Açores, 2006)
This work provides a baseline against which we might measure future changes to oceanic midwater cephalopod stability in the eastern North Atlantic It records a considerable sampling effort from 1959 to 1986 aimed at oceanic midwater cephalopods made by the author and colleagues in the eastern North Atlantic between approximately 10ºN to 70ºN and 0ºto 30ºW. From these samples the latitudinal distribution, the biodiversity and, to some extent, the relative rarity of the species present in the area is shown. Over 700 collections were made with a range of nets from small plankton nets to large commercial trawls of many designs. As an independent measure of the efficiency of our sampling, the species represented by lower beaks from the stomach contents of 241 sperm whales (Physeter catodon) caught or stranded at five different localities in the area are listed and discussed. In total, over 40,000 cephalopods of 82 oceanic midwater species and 16 shelf and slope species were identified and are included here. The number of midwater species caught by nets increases regularly from 11ºN to 32ºN and decreases from 32ºN to 60ºN. A sharp increase at 32ºN of about 10 species above the curve produced by the catches at other stations is very probably due to the use of lights on the nets at this position. This suggests that further use of lights at all stations might elevate the curve at each position commensurate with the numbers of species found by conventional nets. The number of midwater cephalopods caught by nets in each of the 32 families show that Cranchiidae are by far the most numerous (and speciose) followed by Pyroteuthidae and Enoploteuthidae at half the number. 18 families numbered less than 100 individuals. Families eaten by sperm whales showed that Histioteuthidae was by far the most numerous (22787) with Cranchiidae (3285), Octopoteuthidae (1710) and Cycloteuthidae (1360) following in importance. Architeuthidae was not caught by nets but was present in the whale diet (221). The scarcity and expense of net collections suggests that estimates of cephalopod distribution and relative numbers should rely more on analysis of the diet of predators than on net catches. The value of monitoring cephalopods in the deep ocean is discussed.